Long-term, naturalistic treatment with olanzapine, risperidone, quetiapine, or haloperidol monotherapy: 24-month results from the intercontinental schizophrenia outpatient health outcomes (IC-SOHO) study - Lee, P.; Kim, C.E.; Kim, C.Y.; Lin, W. W.; Habil, H.; Dyachkova, Y.; McBride, M.; Dossenbach, M. (2008)
Objective. To compare the effectiveness of olanzapine, risperidone, quetiapine, or haloperidol monotherapy in patients with schizophrenia who were treated in routine clinical practice settings for a period of 2 years. The incidence and persistence of adverse events encountered during long-term therapy are also reported. Method. Outpatients with schizophrenia who entered this 3-year, prospective, observational study were classified according to their initially prescribed antipsychotic monotherapy: olanzapine (n=3222), risperidone (n=1116), quetiapine (n=189), or haloperidol (n=256). Patients were included in the analysis for as long as this treatment was maintained. Results. Over 2 years, olanzapine recipients had significantly (P0.001) greater reduction in overall CGI-S score (and the negative, depressive, and cognitive symptoms domains), lower incidence of sexual and motor dysfunction, and greater odds of response compared to risperidone or haloperidol-treated patients. However, olanzapine patients gained more weight than patients in other treatment groups. The incidence of motor dysfunction was significantly (P0.001) greater in haloperidol-treated patients, relative to the atypical treatment groups. Conclusion. The results of this observational study indicate that, in these patients with schizophrenia, long-term monotherapy with olanzapine may offer benefits over risperidone and haloperidol, but the potential for weight gain should be considered in the clinical management of these patients.